Prospects for Shallots Agribusiness Development in Pamekasan Regency - Ary Bakhtiar; Mulia Salsabila; Mohd Fauzi bin Kamarudin (Badan Penerbitan Fakultas Pertanian, Universitas Bengkulu, 2025)
Shallots have a strategic role in the local economy. Shallots are a staple food and essential seasoning, leading to high demand and strong market potential. As Indonesia is an agricultural country with rich natural resources, shallot farming can improve national food security and fulfil people's food needs. The research applies a descriptive quantitative method using trend analysis to examine shallot production in Pamekasan Regency. The data used are secondary production data from 2020 to 2023. This study aims to determine a. what factors influence the development of shallot farming in Pamekasan Regency, b. the prospects for developing shallot farming in Pamekasan Regency. The results showed that a. there are factors that dominate shallot production in Pamekasan Regency, such as land area, weather, fertilizer problems and agricultural technology. Shallots production data in Pamekasan Regency from 2020 to 2023 shows a significant downward trend. The area of shallot land in Pamekasan Regency is dominated by an area of less than equal to 1 Ha, so if there is a change in cropping patterns or farmers' attitudes in deciding which commodity to plant, it directly affects the level of shallot production. B. Shallots have high economic value and stable domestic and international demand. With appropriate planting and management patterns, shallots will become a commodity that can survive in the rainy and dry seasons. Onion derivative products, such as fried shallots, shallots paste, and shallots powder, have the prospect of increasing added value and farmers' income.